The Relationship of Osteoprotegerin, Matrix Gla Protein, and HbA1C in Controlled and Uncontrolled Type 2 Diabetes Mellitus Patients - Dwi Yuniati Daulay (Indonesian Biomedical Journal, 2010)
BACKGROUND: Many studies have reported that diabetes mellitus correlates with vascular calcification event that increases progressively in uncontrolled diabetes. Osteoprotegerin (OPG) is known to act as a promoter in vascular calcification, contrary to Matrix Gla Protein (MGP), which is an inhibitor in vascular calcification. The aim of this study was to observe the progress of vascular calcification in uncontrolled diabetes patients by assessing biochemical markers OPG as promoter and MGP as inhibitor in vascular calcification. METHODS: This was an observational study with cross sectional design on adult male patients with type 2 diabetes mellitus, defined by DM Consensus Criteria Indonesia, 2006. RESULTS: The results of this study showed that there was a positive significant correlation between OPG and HbA1c (r=0.261, p=0.030), in contrast with MGP that showed no significant correlation with HbA1c. OPG also correlated significantly with Fasting Plasma Glucose (r=0.261, p=0.014). In uncontrolled diabetes group there was positive significant correlation between OPG and HbA1c (r=0.397, p=0.014). There was no significant difference found in the levels of OPG in controlled and uncontrolled diabetes groups (p=0.567), but OPG/MGP index showed higher difference (p=0.259). The OPG/MGP index also had positive significant correlation with HbA1c (r=0.285, p=0.018) and Fasting Plasma Glucose (r=0.313, p=0.009). CONCLUSIONS: This study suggested progress to vascular calcification in uncontrolled type 2 diabetes mellitus. The use of vascular calcification biomarkers are recommended to predict/detect vascular calcification event in type 2 diabetes mellitus patients. KEYWORDS: type 2 diabetes mellitus, vascular calcification, OPG, MGP, HbA1c.